Perlunya Reformasi Kultural di Kepolisian Republik Indonesia - Ahmad Fityan Abdussalam; Hamidah Abdurrachman; Achmad Irwan Hamzani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The purpose of this study is the need for cultural reforms to be carried out in the Indonesian National Police (Polri), efforts to reform police culture in the grand design road map for reform of the police bureaucracy, examines policy efforts to revitalize Polri's human resources and the obstacles associated with the Inspector General FS case. This type of research includes library research. While the approach used is a normative approach. This study uses secondary data obtained from laws and regulations, books and scientific journals. The results of this study indicate that the police reform policy in the cultural aspect associated with bureaucratic reform includes: changes in doctrine and main guidelines, formulation of behavioral guidelines; and empowerment of non-commissioned officers and enlisted police officers in Community Police (Polmas) efforts; Quick wins program and revitalization of Polri's human resources. Polri needs to re-inculcate and re-orient the guidelines and principles established by the police both in the education and care of every member of the Polri and for Polri to take concrete steps by creating special instruments other than a code of ethics that regulates the corps mental conduct so that actions "cover up colleagues' mistakes" and "force solidarity" which in turn has an impact on improving the image of the Polri institution in society.Keywords: Cultural reform, Polri, revitalization. AbstrakTujuan penelitian ini adalah perlunya reformasi kultural yang dijalankan di Kepolisian Republik Indonesia (Polri), upaya reformasi kultural polri dalam road map grand desain reformasi birokrasi polri, mengkaji upaya kebijakan revitalisasi sumber daya manusia polri berserta kendalanya dikaitkan dengan kasus Irjen FS. Jenis penelitian ini termasuk  penelitian pustaka (library research). Sedangkan pendekatan yang digunakan adalah pendekatan normatif.  Penelitian ini menggunakan data sekunder yang diperoleh dari peraturan perundang-undangan, buku dan jurnal ilmiah. Hasil penelitian ini menunjukan bahwa kebijakan reformasi Polri dalam aspek kultural yang dihubungkan dengan reformasi birokrasi tersebut diantaranya adalah: perubahan doktrin dan pedoman induk, perumusan pedoman perilaku; dan pemberdayaan bintara dan tamtama Polri dalam upaya Polisi Masyarakat (Polmas); Program quick wins dan revitalisasi SDM Polri. Polri perlu menanamkan kembali dan re-orientasi pedoman dan prinsip yang dibentuk oleh kepolisian baik dalam pendidikan dan perawatan setiap insan anggota Polri dan agar Polri membuat langkah konkrit dengan membuat instrument khusus selain kode etik yang mengatur tata perilaku jiwa korsa agar tindakan “menutupi kesalahan sejawat” dan “solidaritas angkatan” yang selanjutnya berdampak pada membaiknya citra institusi Polri di tengah masyarakat.Kata Kunci: Reformasi kultural, Polri, revitalisasi.